EFFECT OF SOME PlANT GROWTH REGULATORS ON TOTAL ALKALOIDS PRODUCTION OF ASHWAGANDHA (Withania somnifera L.) In Vitro - & Majeed, Hamood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was conducted in the tissue culture laboratory, College of Educated For Pure Science, Diyala Uinversity in 2014-2015,to investigate the influences of some plant growth regulators on total alkaloids production for ashwagandha plant )Withania somnifera L.) In Vitro .Four concentrations of Benzyl Adenine)BA (0.0, 1, 2 and 3 mg.l-1, which were represented with A0 ،A1 ، A2 and A3 respectively، and also four concentrations of Salicylic acid 0, 10, 20, and 30 mg.l-1 which were represented with B0, B1,B2 and B3 respectively, with the interaction among of Benzyl Adenine and Salicylic acid,these are concentrations added to growing media(MS) in multiplication stages. Seeds were soaked with gibberellic acid 500 mg.l-1 for 18 h at room temperature in the all treatments. Benzyl Adenine at 1 mg.l-1 significantly increased branches number 4.22 branch, and Chlrophyll content 34.07 (SPAD Unit),there is no significant differences at 2 mg.l- in leaves number12.05 ,11.32 leaf, fresh and dry matter of vegetative system 1.42, 1.40g, and 0.134, 0.128 g, also SA at 10 mg.l-1 led to increased in number of branches 3.45 branch, number of leaves 14.05 leaf, dry weight of vegetative system 0.140 g , fresh and dry weight of root system 0.76 ,0.06 g respectively, there is no significant differences at 20 mg.l- in Chlrophyll content 33.77, 35.47(SPAD Unit), fresh weight of vegetative system,1.47, 1.40g, number of roots 18.00,20.10, and percentage of rooting 7.89% ,8.51%. Interaction among of Benzyl Adenine and Salicylic acid (A1B1) shows a significant superiority in all studed vegetative characters, there is no significant differences with (A2B1) in leaves number15.30, 14.80 leaf, fresh weight of vegetative system1.61,1.59 g, dry weight of vegetative system 0.160 ,0.160 g, A0B1 treatment which rooted gave 0.105 mg.g-1 total alkaloids. Benzyl Adenine at 2 mg.l-1 increased total alkaloids 0.091 (mg.g-1), Salicylic acid at 10 (mg.l-1) increased total alkaloids0.091 (mg.g-1 ),also Interaction of treatments A2B1 and A1B1 show a significant superiority of total alkaloids 0.101, 0.100 (mg.g-1) as compared with A0B0 which gave lowest content 0.029 (mg.g-1).